SELECTION OF VEGETATIVE AND GENERATIVE CHARACTERS OF ARABICA COFFEE BY USING SEQUENTIAL PATH ANALYSIS AND STRUCTURAL EQUATION MODELS - WARDIANA, EDI; PRANOWO, DIBYO (Pusat Penelitian dan Pengembangan Perkebunan)
ABSTRACTInterrelations among vegetative, generative and yield characters incoffee plantation is important in breeding and selection programs.Interrelationships among these characters are the causal model and it canbe analyzed by Sequential Path Analysis (SPA). This research was carriedout at Pakuwon Experimental Station located at 450 m above sea level, inLatosol soil type with B type of climate, from December 2010 to April2012. The objectives of this research is to analyze the direct or indirectinfluence of several vegetative and generative characters on yieldcharacters of Arabica coffee through the application of SPA and StructuralEquation Models (SEM). The observation method with systematicsampling on 40 Arabica coffee plants of Kartika 1 and Kartika 2 varietieswere used in this study. The results showed that the number of cherries ofArabica coffee var. Kartika 1 and 2 population in Pakuwon ExperimentalStation were affected directly by generative and indirectly by vegetativecharacters. Plant height and stem girth can be used as positive selectioncriteria for high yielding at vegetatite phase, while the character of widthcanophy can be used as negative selection criteria. In generative phase, thecharacter of quantity of productive branches and the amount of berries andflower cluster can be used as positive selection criteria.Keywords: Coffea arabica, selection, vegetative, generative, yield,sequential path analysis, structural equation modelsABSTRAKKeterkaitan antara karakter vegetatif, generatif dan hasil padatanaman kopi merupakan hal penting dalam program pemuliaan danseleksi. Model saling keterkaitan antar karakter tersebut adalah modelsebab-akibat dan dapat dianalisis melalui Analisis Lintasan Bertahap(ALB). Penelitian ini dilakukan di Kebun Percobaan Pakuwon, padaketinggian tempat 450 m dpl, jenis tanah Latosol, dan tipe iklim B, mulaibulan Desember 2010 sampai April 2012. Tujuan penelitian adalah untukmenganalisis beberapa karakter vegetatif dan generatif yang berpengaruhterhadap karakter hasil tanaman kopi Arabika melalui penggunaan ALBdan Model Persamaan Struktural (MPS). Metode yang digunakan adalahmetode observasi dengan teknik penentuan pohon contoh secara sistematissebanyak 40 tanaman kopi Arabika varietas Kartika 1 dan Kartika 2. Hasilpenelitian menunjukkan bahwa jumlah buah pada populasi kopi Arabikavarietas Kartika 1 dan 2 di KP Pakuwon dipengaruhi secara langsung olehkarakter generatif dan secara tidak langsung oleh karakter vegetatif. Padafase vegetatif, karakter tinggi tanaman dan diameter batang dapatdigunakan sebagai kriteria seleksi positif untuk produksi tinggi,sedangkan karakter lebar tajuk dapat digunakan sebagai kriteria seleksinegatif. Pada fase generatif, karakter jumlah cabang produktif serta jumlahklaster buah dan bunga dapat digunakan sebagai kriteria seleksi positif.Kata kunci: Kopi arabika, seleksi, vegetatif, generatif, hasil, analisislintasan bertahap, model persamaan struktural